Positron emission tomography in the detection of occult primary head and neck carcinoma: a retrospective study - Pereira, G (2013)
BACKGROUND: The management of cervical lymph node metastases from an unknown primary tumor remains a controversial subject. Recently, Positron Emission Tomography (PET) has proved useful in the detection of these tumors, even after an unsuccessful conventional diagnostic workup. This study was performed to assess the role of PET in the detection of occult primary head and neck carcinomas. METHODS: A retrospective analysis of a four year period at a tertiary referral oncology hospital was conducted. RESULTS: Of the 49 patients with cervical metastases of carcinoma from an unknown primary, PET detected a primary in 9 patients and gave 5 false positive and 4 false negative results. Detection rate, sensitivity, specificity and accuracy were of 18.4%, 69.2%, 86.1% and 81.6%, respectively. PET was also of substantial benefit in detecting distant metastatic disease and, thus, altered therapeutic strategies in a significant amount of patients. CONCLUSIONS: Therefore, PET is a valuable tool in the management of patients with occult primary head and neck carcinoma, not only because it provides additional information as to the location of primary tumors, but also due to the fact that it can detect unexpected distant metastases